Expression of Bcl‐2 19‐kDa interacting protein 3 predicts prognosis after ampullary carcinoma resection. (3rd July 2016) - Fujimoto, Takaaki; Ohtsuka, Takao; Date, Kenjiro; Kimura, Hideyo; Matsunaga, Taketo; Mori, Yasuhisa; Miyasaka, Yoshihiro; Mochidome, Naoki; Oda, Yoshinao; Nakamura, Masafumi
Abstract: Background: An adequate management strategy for ampullary carcinoma (AC), a rare neoplasm, has yet to be determined. The aim of this study was to identify specific molecular markers allowing for the adequate management of AC. Methods: The clinicopathological data of 41 patients who underwent curative resection of AC were reviewed retrospectively. The expression of thymidylate synthase (TS) and Bcl‐2 19‐kDa interacting protein 3 (BNIP3), two sensitive markers for S‐1 and gemcitabine, respectively, was evaluated immunohistochemically. The relationship between the expression levels of these markers and the clinicopathological data were then investigated. Results: The 5‐year overall survival rate in the study population was 62%. In univariate and multivariate analyses, lymph node metastasis, neural invasion, lymphatic invasion, and the high‐level BNIP3 expression were significant predictive factors for a poor postoperative prognosis. Neither TS nor BNIP3 expression were able to predict survival or the disease recurrence rate in patients who received postoperative adjuvant chemotherapy for AC. Conclusions: BNIP3 expression may serve as a prognostic marker for patients with AC, but neither TS nor BNIP3 contributes to the selection criteria for adjuvant chemotherapy for AC, at least with respect to current drug regimens. Abstract : Highlight Aiming to establish an adequate management strategy for this rare neoplasm, Fujimoto and colleagues demonstrated that expression of Bcl‐2 19‐kDa interacting protein 3 (BNIP3), a sensitive marker for gemcitabine, may serve as a prognostic marker for ampullary carcinoma, although it does not contribute to the selection criteria for adjuvant chemotherapy.